Lysozyme-stabilized Ag nanoclusters: synthesis of different compositions and fluorescent responses to sulfide ions with distinct modes. Issue 70 (12th July 2016) - Gao, Zhidan; Liu, Fang; Hu, Ruoxin; Zhao, Meiping; Shao, Na
Abstract : The effect of composition on the photoluminescence properties of lysozyme-stabilized Ag nanoclusters and their sensing modes for sulfide anions were studied. Abstract : In this study, three red-emissive Ag nanoclusters capped with denatured lysozyme (dLys-AgNCs1–3 ) were synthesized from different reactant molar ratios of AgNO3 and lysozyme. dLys-AgNCs1 contained only Ag(0), whereas dLys-AgNCs2 and3 contained both Ag(0) and Ag(i ). The maximum emission wavelengths of dLys-AgNCs1–3 were all near 640 nm when excited at 490 nm, but had different photoluminescence intensities. The photoluminescence properties of the dLys-AgNCs in the presence of common inorganic anions were studied. dLys-AgNCs1–3 had a distinct photoluminescence response to S 2− . The photoluminescence of dLys-AgNCs1 was quenched by S 2−, because S 2− destroyed the nanostructure of dLys-AgNCs1 by forming Ag2 S. The photoluminescence of dLys-AgNCs3 was enhanced by S 2−, because S 2− bound to Ag(i ) in dLys-AgNCs3 and altered the ligand-to-metal–metal charge transfer. For dLys-AgNCs2, the photoluminescence was enhanced with a small amount of S 2− and quenched when more S 2− was added. This was explained by S 2− binding to Ag(i ) at low concentrations and then to Ag(0) at high concentrations. Other anions had no obvious effects, except that I − quenched the photoluminescence of dLys-AgNCs1–3 . The response mechanisms were investigated by XPS, MS, zeta potential, DLS, and fluorescence lifetime measurements. As-prepared dLys-AgNCs1 and3 were used as fluorescent probes for S 2− detection in tap water and lake water with satisfactory results.